2011
DOI: 10.1029/2011gl047046
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal and seasonal dependence of nighttime equatorial plasma density irregularities during solar minimum detected on the C/NOFS satellite

Abstract: During the night in the F region about the equator, plasma density depletions form, causing scintillation. In April 2008, the Communications/Navigation Outage Forecasting System (C/NOFS) satellite developed by the Air Force Research Laboratory was launched to predict ionospheric scintillation. Using its Planar Langmuir Probe (PLP), C/NOFS is capable of measuring in situ ion density within the F region over the equator. Plasma irregularities are found regularly during the night. We examine how these irregularit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
93
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 85 publications
(117 citation statements)
references
References 19 publications
(31 reference statements)
12
93
0
1
Order By: Relevance
“…This is the objective of the present contribution. Therefore, it complements previous work by Roddy et al (2010) and Dao et al (2011), which also analyzed data corresponding to low solar activity conditions. The first authors processed N i /N i records, calculated from the standard deviation N i of ion density fluctuations around its 1 s average N i , to provide statistics of the ability of the C/NOFS PLP to detect scintillation observed by the Scintillation Network Decision Aid (SCINDA) network (Groves et al, 1997) at Christmas Island (3 • N, 157 • W).…”
Section: Introductionmentioning
confidence: 51%
“…This is the objective of the present contribution. Therefore, it complements previous work by Roddy et al (2010) and Dao et al (2011), which also analyzed data corresponding to low solar activity conditions. The first authors processed N i /N i records, calculated from the standard deviation N i of ion density fluctuations around its 1 s average N i , to provide statistics of the ability of the C/NOFS PLP to detect scintillation observed by the Scintillation Network Decision Aid (SCINDA) network (Groves et al, 1997) at Christmas Island (3 • N, 157 • W).…”
Section: Introductionmentioning
confidence: 51%
“…For example, Communication/Navigation Outage Forecasting System (C/NOFS) satellite observations reported by Huang and Hairston (2015) showed that EPBs can be present under weak, and even negative, upward plasma drift conditions. C/NOFS observations during the 2008-2009 solar minimum that were reported by Dao et al (2011) showed convincing evidence that lower atmospheric forcing might play a significant role in EPB generation. In addition to these observations, modeling has shown that R-T growth is still possible under small/negative upward plasma drift conditions (Carter et al 2016) and that EPB development and characteristics can be significantly influenced by the presence of atmospheric gravity waves (Retterer and Roddy 2014).…”
Section: Introductionmentioning
confidence: 79%
“…The smoothed density can be estimated either by a running mean or, if the irregularities expected are overwhelmingly depletions (reductions in density), estimated by the envelope of density maxima spaced on an ambientscale grid throughout the time series. Dao et al (2011) employed similar techniques, but looked solely at N e /N e0 , which is always small in the daytime, to focus on the nighttime irregularities. A sample of this density-irregularity calculation using data from day 281, year 2010, around 18 UT, is shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The C/NOFS satellite was launched in April 2008 as a component of a system to specify and forecast the occurrence of radio scintillations that interfere with the systems that rely on transionospheric radio propagation (de La Beaujardiere et al, 2004). Its orbit was elliptical (400 × 850 km) with low inclination (13 • ) so as to sample the ionospheric plasma in the region near the geomagnetic equator, one of the regions where the density irregularities responsible for the scintillation are found.…”
Section: Discussionmentioning
confidence: 99%